Power Doppler evaluation of revascularization in childhood moyamoya - Perren, Fabienne; Meairs, Stephen; Schmiedek, Peter; Hennerici, Michael G.; Horn, Peter (Neurology, 2005)
Moyamoya disease is generally recognized in young children. One potential treatment is direct extra-intracranial bypass combined with indirect revascularization using encephalo-myo-synangiosis. Standard follow-up to assess neoangiogenesis includes repeat cerebral angiography, which is invasive. The authors studied whether noninvasive power Doppler imaging could evaluate the patency of the bypass and the degree of indirect revascularization. They found that transcranial power Doppler imaging is a valid noninvasive alternative to cerebral angiography.
Gesehen am 12.05.2022